Kategorisasi Pemaknaan Lafadz Nazhara dalam Surat Al-Naml Perspektif Musthafa Al-Maraghi - Alfiyatul Azizah; Nabil Nabil (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Categorization of the Meaning of Lafadz Nazhara in Surah Al-Naml from the Perspective of Mustafa Al-MaraghiThis study aimed to determine the meaning of lafaz nazhara in Surah An-Naml according to Ahmad Musthafa al-Maraghi, in his book that titled Tafsr Al-Marâghî. This research is a library research that uses a qualitative approach. The analysis technique used is content analysis using the thematic method. The data of this study were taken from the Tafsr Al-Marâghî book on the word of nazhara in the surah An-Naml. This study concluded that, Ahmad Musthafa al-Maraghi categorizes the meaning of lafadz nazhara in An-Naml's letter into three categories, namely; first, word nazhara spoken by Allah SWT to disbelievers means an order to pay attention to the power of Allah SWT, as well as a threat from Allah SWT for their disbeliefer, second, word nazhara spoken by fellow humans who have the same level, meaning as an order to consider decisions, and can also be used as a test to find out the truth, while the third, word nazhara which are spoken by fellow creatures but have different positions, that is, to test someone's honesty, and can also be a command to understand some information